5 Developing a novel stent concept in the management of bifurcation disease. (24th April 2016) - Banning, AS; Garitey, V; Mouniemne, K; Gershlick, AH
Abstract : Introductions: Provisional stenting is the accepted treatment for bifurcation disease, but techniques and stents for 1:1:1 disease can give sub-optimal results. We have developed a novel stent designed to be balloon modified in-situ to any bifurcation angle with no ingression of stent material into the main or side-branch lumen. Methods: Following design discussions, and extensive Finite Element Analysis studies with our non-commercial Industry partner two prototype (ST04 and ST05) were laser cut from cobalt chromium. In-vitro testing included detailed quantitative Micro-CT and video evaluation in silicone bifurcation models of 2 shapes (λ, Y) and 3 angles (45o, 60o, 75o), n = 36. Prototypes were assessed for crush resistance. Results: Both prototypes showed successful longitudinally shortening (Figure 1 ). Mean distance from stent strut to vessel wall  was 0.11+/-0.04mm (ST04), 0.09+/-0.02mm (ST05) in λ-60o indicating excellent apposition, with no protrusion into either lumen. Crush resistance in the malleable part was lower than the standard section (eg: ST04 malleable end = 0.13+/-0.01N/mm; regular part=0.32+/-0.01N/mm p < 0.001). Conclusions: The results show proof-of-concept that a stent with a malleable end can be conformed to the side branch ostium with good apposition. This may translate into better outcomes for two-stent strategies in true bifurcation lesions.